2002
DOI: 10.1094/phyto.2002.92.11.1189
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora infestans Populations from Tomato and Potato in North Carolina Differ in Genetic Diversity and Structure

Abstract: Phytophthora infestans causes a destructive disease on tomato and potato. In North Carolina (NC) potatoes are mostly grown in the east, whereas tomatoes are grown in the mountainous areas in the western part of the state. Five genotypes of P. infestans were identified from 93 and 157 isolates collected from tomato and potato over a 5 year period between 1993 and 1998. All isolates collected from potato in eastern NC were the US-8 genotype, whereas only a single isolate was the US-1 genotype. Tuber blight was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…; Wangsomboondee et al. ; Lees et al. ), elimination of sources of inoculum, use of decision support systems to determine when to apply fungicides and host resistance will help tomato growers to reduce crop losses caused by this disease.…”
Section: Discussionmentioning
confidence: 99%
“…; Wangsomboondee et al. ; Lees et al. ), elimination of sources of inoculum, use of decision support systems to determine when to apply fungicides and host resistance will help tomato growers to reduce crop losses caused by this disease.…”
Section: Discussionmentioning
confidence: 99%
“…() and Wangsomboondee et al . (), tomato and potato samples often came from different geographical regions, weakening any conclusion as to the effect of host on sample composition. In the present study, both potato and tomato samples were collected from throughout Great Britain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In many global regions where multiple P. infestans genotypes and multiple host species are present, some degree of host specialization has been observed, both in terms of the frequency of recurrent clonal lineages on each host, and in terms of within-lineage genotypic and phenotypic variation. For example, multiple studies in the USA have demonstrated that the US-8 lineage is common on potato, but very seldom infects tomato (Wangsomboondee et al, 2002;Danies et al, 2012;Peters et al, 2014). In studies where inoculations onto tomato and potato leaflets have been carried out, isolates are often found to be more aggressive on one host than another.…”
Section: Introductionmentioning
confidence: 99%
“…The increased complexity of P. infestans populations has coincided with the emergence of aggressive genotypes with fungicide resistance (Goodwin et al 1995(Goodwin et al , 1996. For example, the metalaxyl resistant US-11 genotype (A1 mating type) devastated both tomato and potato crops in the United States in 1996 and 1997 (Gavino et al 2000;Derie and Inglis 2001;Wangsomboondee et al 2002). The US-11 genotype originated as an especially fit recombinant of the US-6 and US-8 genotypes and displaced both the US-1 and US-6 genotypes.…”
Section: Evolution Of Late Blight Populations In United States and Camentioning
confidence: 99%